Biosynthesis of mercapturic acid derivative of the labdane-type diterpene, cyslabdan that potentiates imipenem activity against methicillin-resistant Staphylococcus aureus: cyslabdan is generated by mycothiol-mediated xenobiotic detoxification. (1st March 2016) - Ikeda, Haruo; Shin-ya, Kazuo; Nagamitsu, Tohru; Tomoda, Hiroshi
Abstract: Genome mining of cyslabdan-producing Streptomyces cyslabdanicus K04-0144 revealed that a set of four genes, cldA, cldB, cldC, and cldD (the cld cluster), which formed a single transcriptional unit, were involved in the biosynthesis of cyslabdan that potentiates imipenem activity against methicillin-resistant Staphylococcus aureus . Experimental studies supported the heterologous expression of the cld cluster of S. cyslabdanicus K04-0144 in S. avermitilis SUKA22, and transformants carrying the cld cluster produced not only cyslabdan A (1 ), but also its new derivatives, 17-hydroxyl-1 (2 ) and 2-hydroxyl-1 (3 ), in the culture broth. An analysis of diterpene metabolites in the mycelia showed that a large amount of a novel intermediate had accumulated and its structure was elucidated as ( 7S, 8S, 12E )-8, 17-epoxy-7-hydroxylabda-12, 14-diene (4 ). The cld -like cluster ( rmn cluster) was also detected in the genome of S. anulatus GM95 by searching our in-house genome databases, and the heterologous expression of the rmn cluster in S. avermitilis SUAK22 demonstrated that the rmn cluster was involved in the biosynthesis of the labdane-type bicyclic diterpene, raimonol (7 ). CldA/RmnA catalyzed the generation of geranylgeranyl diphosphate (GGPP) from dimethylallyl diphosphate and isopentenyl diphosphate. CldB/RmnB converted GGPP to (+)-copalyl diphosphate, and CldD/RmnD generated labda-8(17), 12( E ), 14-triene (5 ). CldC introduced two oxygen atoms at C-7 and C-8, 17 to generate 4, while RmnC hydroxylated 5 at C-7 to generate 7 . The heterologous expression of the cld cluster suggested that four gene products catalyzed to generate 4, but not 1 . The deletion mutant of the gene encoding the mycothiol (MSH)- S -conjugate amidase ( mca ) of S. avermitilis SUKA22 carrying the cld cluster failed to produce 1, but accumulated 4 in the mycelia, whereas S. avermitilis SUKA22 and its mca -deletion mutant carrying the cld cluster both produced the MSH- S -conjugate of 4 . The intermediate 4 was converted into the MSH- S -conjugate with MSH, which was achieved through a non-enzymatic nucleophilic reaction. The MSH- S -conjugate of 4 generated was further hydrolyzed to generate the mercapturic acid derivative, 1, by MSH- S -conjugate amidase and 1 was excreted from the mycelia.